Interactive radio for development - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
On the African Learning Channel, genuine listener interaction is key to bringing the message home. The ALC, a project of the World Space Foundation, makes collective use of one of the digital broadcast channels of the World Space satellite networks...